2005
DOI: 10.2320/matertrans.46.2886
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and Crystallization Behavior of the Zr<SUB>50</SUB>Cu<SUB>40</SUB>Al<SUB>10</SUB> Metallic Glass

Abstract: We examined relaxation and crystallization behavior of the ternary Zr 50 Cu 40 Al 10 metallic glass by using positron annihilation and transmission electron microscopy (TEM). Observed changes in positron annihilation lifetime of the alloy annealed isothermally at 673 K, which is below the glass transition temperature, correlate well with observed density changes; while coincidence Doppler broadening (CDB) spectra exhibit no significant change. These observations demonstrate that free volume decreases without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…As shown in this figure, the difference of positron lifetime comparing with as-prepared sample increases with increasing annealing temperature. This result agrees with our previous results [4,9,10]. As can be seen from this figure, density increases, and absolute value of positron lifetime decreases with increasing annealing temperature.…”
Section: Methodssupporting
confidence: 83%
“…As shown in this figure, the difference of positron lifetime comparing with as-prepared sample increases with increasing annealing temperature. This result agrees with our previous results [4,9,10]. As can be seen from this figure, density increases, and absolute value of positron lifetime decreases with increasing annealing temperature.…”
Section: Methodssupporting
confidence: 83%
“…This tendency is also observed at 673 K, which is just below the T g . 9) These results demonstrate that the local chemical environment around the free volume remains essentially the same during the relaxation process; namely, no long-range diffusion around the free volume takes place in spite of the decrease in the free volume. Saida et al, have reported that the icosahedral local structure exists in Zr-based ternary and binary metallic glasses, and they does not indicate significant change in local structure during nanoquasicrystallization.…”
Section: Resultsmentioning
confidence: 72%
“…Numerous further studies [21][22][23][24] have also observed the formation of nano-crystalline spherulites during the devitrification of both binary and multicomponent component metallic glass systems. In virtually all cases the spherulites are homogenously distributed within the amorphous matrix, with a radial growth originating from the centre of nucleation sites.…”
Section: Introductionmentioning
confidence: 96%
“…Yano et al [21] observed the formation of spherulites in a Zr 50 Cu 40 Al 10 bulk metallic glass forming alloy via TEM and positron annihilation lifetime measurements. Upon annealing at 773 K, crystallisation proceeded through the formation of spherical agglomerates of radially developing crystallites, about 600 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%